Do informal workers queue for formal jobs in Brazil? - Fábio Veras Soares (Institute for Applied Economic Research (ipea), 2015)
This paper investigates the existence of a job queue for formal (registered) jobs in the Brazilian labour market in an endogenous switching regression framework. This approach aims at correctly specifying the allocation process in the presence of queuing and getting unbiased wage equation estimates in order evaluate the role of wage differential between formal and informal sector in determining sector allocation. We estimate three types of bivariate probit specifications in order to evaluate the sensitivity of the results to different assumptions about the sector allocation process. In particular, we assess the sensitivity of the job queue estimates to the usual assumption of partial observability using subjective survey questions on the desire of informal (non-registered) workers to switch to formal job. Our tests were not able to reject the hypothesis of job queue. Our estimates of the job queue "length" for selected groups show that non-white, female, illiterate, "new entrants" and former informal workers are the groups with the lower probability of being chosen from the queue conditional on being in the queue. This result is particularly strong for workers whose last job was in the informal sector, suggesting that a spell in the informal sector may jeopardize the worker's chance of getting a formal job.
Keywords: 330